ANALISIS FAKTOR KESULITAN SISWA DALAM PENGUASAAN KOSAKATA BAHASA SASAK DALAM PEMBELAJARAN MUATAN LOKAL KELAS VI SEKOLAH DASAR DWIJENDRA MATARAM - Nuba Sanzania; Muhammad Tahir; Muhammad Sobri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the factors that cause students to experience difficulties in mastering Sasak language vocabulary and the efforts made by teachers to overcome students' difficulties. The subjects in this research were 13 people, including 12 class VI students and a teacher who was the class teacher and person responsible for local content learning in class VI at the Dwijendra Mataram Elementary School. Data collection methods were carried out by means of interviews and documentation. The data analysis technique used is Miles and Huberman with data analysis components reduction, presentation and drawing conclusions. The results of this research show that there are 3 factors that cause students to experience difficulties in mastering vocabulary, lack of student interest, lack of support from the social environment, and differences in vocabulary used daily and in local content learning books. Apart from that, it was also found that the efforts made by teachers to overcome students' difficulties were by providing vocabulary notes and utilize cultural Saturday activities as a means to introduce Sasak language to students by creating activities that involve students and use Sasak language.